Comparison of different scoring systems for outcome prediction in patients with Fournier's gangrene: Experience with 50 patients. (August 2014) - Tuncel, Altug; Keten, Tanju; Aslan, Yilmaz; Kayali, Mustafa; Erkan, Anil; Koseoglu, Ersin; Atan, Ali
Abstract Objective. The aim of this study was to evaluate effective factors in the survival of patients with Fournier's gangrene (FG) and compare three different validated scoring systems for outcome prediction: Fournier's Gangrene Severity Index (FGSI), Uludag Fournier's Gangrene Severity Index (UFGSI) and age-adjusted Charlson Comorbidity Index (ACCI). Material and methods. Fifty men who underwent surgery for FG between July 2005 and August 2012 were included in the study. Data were collected on medical history, symptoms, physical examination findings, vital signs, admission and final laboratory tests, timing and extent of surgical debridement, and antibiotic treatment used. The FGSI, UFGSI and ACCI were evaluated stratified by survival. Admission and final parameters were measured using the Mann–Whitney test. Results. The results were evaluated for two groups: survivors (n = 43) and non-survivors (n = 7). Survivors were younger than non-survivors (median age 58 vs 68.5 years, p = 0.017). The median extent of body surface area involved in the necrotizing process in patients who survived and did not survive was 2.3% and 4.8%, respectively (p = 0.04). No significant differences in laboratory parameters were found between survivors and non-survivors at the time of admission, except for haemoglobin, haematocrit, serum urea and albumin levels. Only UFGSI, but not FGSI or ACCI, had any meaning or predictive value in disease severity or patients' survival. Conclusion. Only the UFGSI score could predict the disease severity and the patients' survival. The findings did not support previous findings that an UFGSI threshold of 9 is a predictor of mortality during initial evaluation.